Insecticide Effects on Membrane Potential of Catfish Egg Cell (Clarias batrachus) - Unggul Punjung Juswono; Kusharto Kusharto; Yeni Cahyati; Risalatul Latifah (Natural B, Journal of Health and Environmental Sciences, 2012)
Pollution has been occured in our environment due to daily life waste, industrial and using of peptiside in agroindustrial farm. Over usuage and dose of peptiside could be harmfull to the farm environment especially for fish farm. Measurement of membrane potential of fish egg cells is a simple metode to investigate water polution level. Membrane potential of fish egg cells can be measured using microelectrode probe which is connected to an electrometer. The changing of membrane potential value indicate the level of water polution. Variation of peptiside concentrations cause the changing of potential membrane value. Increasing of peptiside concentration cause decreasing of potential membrane. Its may due to some blocking of channel and other protein by peptiside molecule so the permeability of membrane to ions is decrease. The results of our experiment show that the increasing of peptiside concentration cause decreasing of the membrane potential value. For peptiside concentration of 0.4% decrease potential membrane to -28 ± 5 mV. It means that the increasing peptiside concentration cause significanly decrease in potential membrane which may be used for prediction of water polution level.